Efficient conversion of acids and esters to amides and transamidation of primary amides using OSU-6. Issue 48 (2nd December 2015) - Nammalwar, Baskar; Muddala, Nagendra Prasad; Watts, Field M.; Bunce, Richard A.
Abstract: OSU-6, an MCM-41 type hexagonal mesoporous silica with strong Bronsted acid properties, has been used to promote the high-yield conversion of carboxylic acids and esters to carboxamides as well as transamidations of primary amides in a one-pot solventless approach. A metal-free heterogeneous catalyst that promotes all of these processes has not been previously reported. OSU-6 enables these transformations to proceed in shorter times and at lower temperatures for a broad range of substrates. An added benefit is that the catalyst can be recycled and reused multiple times without significant loss of activity. Graphical abstract: